Association of Circulating Tumor DNA (ctDNA) to Monitoring Treatment Response in Urothelial Carcinoma: A Comprehensive Systematic Review - Muhammad Rizki Fadil; Fabian Gamal Sutrisno; Siti Fira Rahmawaty; Archie Fontana Iskandar (Universitas Muhamadiyah Manado, 2026)
Circulating tumor DNA (ctDNA) has emerged as a promising liquid biopsy biomarker for real-time monitoring of tumor dynamics. In urothelial carcinoma (UC), effective monitoring of treatment response remains a clinical challenge due to the limitations of conventional imaging and invasive procedures. This systematic review aims to synthesize the existing evidence on the association between ctDNA dynamics and treatment response monitoring across various stages and therapeutic settings. A comprehensive systematic review was conducted. We included cohort studies, randomized controlled trials, and meta-analyses that evaluated ctDNA in UC patients undergoing treatment. Data were extracted on patient population, methodology, treatment, sampling strategy, clinical outcomes, and statistical associations. The review encompassed 80 studies. Baseline ctDNA positivity was strongly prognostic, associated with a 4- to 6-fold increased risk of recurrence or death (HR 4.23-6.56). Dynamic ctDNA clearances or significants reduction during treatment, were strongly associated with improved outcomes. Showing hazard ratios for adverse events as low as 0.10-0.31. ctDNA demonstrated time advantages of 53-90 days over radiographic detection. ctDNA is a potent tool for monitoring treatment response in urothelial carcinoma. It provides superior prognostic and offers a significant lead time for detecting treatment failure. Future research must focus on standardizing methodologies and validating ctDNA-guided therapeutic.